1997
DOI: 10.1200/jco.1997.15.5.2067
|View full text |Cite
|
Sign up to set email alerts
|

Survival of differentiated thyroid carcinoma studied in 500 patients.

Abstract: In differentiated thyroid carcinoma, the use of total surgical thyroidectomy followed by high-dose radioiodine therapy and early surgical reintervention in case of locoregional recurrence yields high survival rates, even without adjuvant external radiotherapy of the neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
60
5
9

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 28 publications
16
60
5
9
Order By: Relevance
“…This discrepancy could be the result of etiologic differences that correlate with geography, as reported 10-year and 20-year DSS from Sweden, Germany, and Austria, where goiter is endemic or prevented by iodide substitution, were similar or worse compared with this study. 3,9,38,39 Whereas tumor size (median 50 mm) was slightly higher, the age distribution, which was a major risk factor, was similar in our cohort (median age, 41.3 years in the PTC group) with those reported from countries without endemic goiter (United States, Asia). Studies from regions with endemic goiter, show that the proportion of FTC in patients with WDTC is higher in these regions.…”
Section: Survivalsupporting
confidence: 58%
“…This discrepancy could be the result of etiologic differences that correlate with geography, as reported 10-year and 20-year DSS from Sweden, Germany, and Austria, where goiter is endemic or prevented by iodide substitution, were similar or worse compared with this study. 3,9,38,39 Whereas tumor size (median 50 mm) was slightly higher, the age distribution, which was a major risk factor, was similar in our cohort (median age, 41.3 years in the PTC group) with those reported from countries without endemic goiter (United States, Asia). Studies from regions with endemic goiter, show that the proportion of FTC in patients with WDTC is higher in these regions.…”
Section: Survivalsupporting
confidence: 58%
“…Children and people younger than 20 years tend to present with higher stage disease and greater likelihood of locoregional and distant metastases, despite it, children generally have excellent survival rates, the exception to this rule is the disease in children aged < 10 years (Sipos & Mazzaferri, 2010). In the same line as most of the studies (Beenken et al, 2000;Eichhorn et al, 2003;Gilliland et al, 1997;Lerch et al, 1997;Mazzaferri, 1999;Shah et al, 1992), we found that the presence of distant metastases at presentation is an independent risk factor in the prognosis of differentiated thyroid carcinoma. The main cause of death from differentiated thyroid cancer is distant metastases (Mazzaferri, 1993).…”
Section: Discussionsupporting
confidence: 78%
“…The other nine systems were either derived from DTC (i.e. PTC and FTC together; Cady & Rossi 1988, Mazzaferri & Jhiang 1994, Shaha et al 1994, Lerch et al 1997, Beeken et al 2000, Greene et al 2002, Yildirim 2005 or derived from all histologic types of thyroid carcinoma, including medullary and anaplastic thyroid carcinoma (Byar et al 1979, Sherman et al 1998. Interestingly, there was only one of the 18 systems (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 8 shows CSS of 171 patients by the GAMES system. University of Mü nster (Mü nster; Lerch et al 1997) This system was published in 1995 after an analysis of 500 DTC patients. Of note, this series comprised a high proportion of FTC (almost 40%).…”
Section: B H-h Lang Et Al: Staging For Follicular Thyroid Carcinomamentioning
confidence: 99%